Implementasi Computer Vision untuk Deteksi Truk - Purnama, Bedy; Setyorini, Setyorini; Insanudin, Entik; Ismail, Ismail; Labib, Fahdi; Furqoon, Naufal Sayyid (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
The Banten Province PUPR Service is an implementation element of the provincial government responsible for public works and spatial planning. ODOL (over dimension and over load) trucks were identified as the cause of many damaged bridges. To overcome this problem, the Ministry of Transportation of the Republic of Indonesia provides weighbridge facilities as a recording and monitoring tool to control goods transportation that exceeds capacity. However, there are still drivers who rig the weighbridge, risking endangering driver safety and bridge infrastructure. Therefore, the proposed solution is the application of Computer Vision technology to detect ODOL trucks. This technology promises to empower target communities by increasing the efficiency of truck traffic monitoring, optimizing infrastructure maintenance, and increasing regional security. The application of this technology also provides valuable data and information for decision-making and strategic planning and has the potential to increase local technological capacity and create economic opportunities and partnerships in the transportation and infrastructure sectors. It is hoped that this initiative will have a positive and sustainable impact on the people of the Banten region who are facing challenges in the fields of transportation and infrastructure. This community service activity as a whole will facilitate the Banten Province PUPR Service to create good governance in project financial management and monitor the current structural conditions of the infrastructure that has been built from these projects. It is hoped that through proper implementation, the use of the project budget can be maximized as well as for predictable maintenance of bridge road infrastructure in Banten Province so that resilient infrastructure can be realized in accordance with UN Sustainable Development Goals Number 9, namely Innovation, Industry, and Infrastructure. Community service implementation will take place on Thursday-Friday, 14-15 December 2023, at the Banten Province PUPR Service, Jl. KH Abdul Fatah Hasan No.25, Sumurpecung, Serang District, Serang City, Banten. Representatives of the Telkom University team and the Banten Province PUPR Service attended this event.